2018
DOI: 10.1055/a-0650-4447
|View full text |Cite
|
Sign up to set email alerts
|

EUS fine-needle pancreatic core biopsy can determine eligibility for tumor-agnostic immunotherapy

Abstract: Background and study aims  The US FDA recently approved a cancer treatment with pembrolizumab based upon the tumor biomarker status of deficient mismatch repair (dMMR) rather than a specific disease-based approach. We sought to determine if endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) could determine dMMR and quantification of PD-L1 expression to potentially guide the delivery of tumor agnostic immunotherapy. Patients and methods  Immunohistochemistry was performed on archived pancreas core biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Additionally, the tissue obtained via FNB can be helpful in molecular profiling of the tumor and evaluation of biomarkers to aid in the management of the patient. A recent study concluded that EUS‐FNB specimens of PDAs were adequate for mismatch repair protein and programmed death ligand‐1 immunohistochemistry in 97.2% and 94.9% cases, respectively . Tiriac and colleagues have even shown that pancreatic cancer organoids can be successfully created from FNB samples at the time of initial tissue diagnosis for enhancing personalized treatment options …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the tissue obtained via FNB can be helpful in molecular profiling of the tumor and evaluation of biomarkers to aid in the management of the patient. A recent study concluded that EUS‐FNB specimens of PDAs were adequate for mismatch repair protein and programmed death ligand‐1 immunohistochemistry in 97.2% and 94.9% cases, respectively . Tiriac and colleagues have even shown that pancreatic cancer organoids can be successfully created from FNB samples at the time of initial tissue diagnosis for enhancing personalized treatment options …”
Section: Discussionmentioning
confidence: 99%
“…In comparison with FNA, FNB may be more useful in diagnosing well-differentiated PDAs as it clearly reveals the histologic architec- concluded that EUS-FNB specimens of PDAs were adequate for mismatch repair protein and programmed death ligand-1 immunohistochemistry in 97.2% and 94.9% cases, respectively. 26 Tiriac and colleagues have even shown that pancreatic cancer organoids can be successfully created from FNB samples at the time of initial tissue diagnosis for enhancing personalized treatment options. 27 In the non-neoplastic group, autoimmune pancreatitis was given a descriptive diagnosis on FNA.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study at least 3% of malignant pancreas lesions were sensitive to pembrolizumab and more than 8% were sensitive to the family of immune checkpoint inhibitors. Due to the large EUS-FNB tissue samples precision immuno-oncology can be applied to these patients (PD-L1 evaluation is performed in large tissue samples) 15. The far upstream element-binding protein 1 (FUBP1) is an important transactivator of c-Myc proto-oncogene.…”
Section: Molecular Pathwaysmentioning
confidence: 99%
“…According to some authors, this procedure is both safe and accurate and it enables pathologists to obtain abundant material to perform morphological diagnosis on and to carry out immunohistochemical analyses especially in difficult cases like well-differentiated adenocarcinomas, mesenchymal tumors, autoimmune pancreatitis, or lymphoma [10]. Moreover, the preservation of histological material may guarantee, in the near future, the possibility to test it for novel targeted therapies [3, 11, 12]. Despite numerous published data, it remains unclear which is the best method to apply, therefore, we propose to compare FNA and FNB procedures or their combination to understand which could be the most appropriate 1 to choose.…”
Section: Introductionmentioning
confidence: 99%